Impact of a Single 36 Hours Prolonged Fasting Period in Adults With Type 1 Diabetes – A Cross-Over Controlled Trial - Moser, Othmar; Eckstein, Max L.; Mueller, Alexander; Tripolt, Norbert J.; Yildirim, Hakan; Abbas, Farah; Pferschy, Peter N.; Goswami, Nandu; Aberer, Felix; Obermayer, Anna; Pieber, Thomas R.; Kojzar, Harald; et al. (Frontiers in Endocrinology, 2021)
Prolonged fasting has shown beneficial effects in healthy individuals and in people with chronic diseases. In type 1 diabetes, the effect or even the feasibility of fasting is unclear. We aimed to assess the impact and safety of prolonged fasting in adults with type 1 diabetes. Glycemia was assessed during overnight fasting (12 hours) vs. prolonged fasting (36 hours) via an intermittently-scanned continuous glucose monitoring system. Anthropometric data, metabolic and hormonal markers were compared between both trial arms. After each fasting period, a 75 g oral glucose tolerance test was performed and plasma glucose levels and hormones were assessed. Data were compared via paired t-tests and mixed-model regressions (p≤0.05). Twenty individuals with type 1 diabetes (7 females) with a mean±SD age of 35±11 years, body mass index (BMI) 24.8±2.8 kg/m2 and HbA1c 54±7 mmol/mol were included. Hypoglycemia/hour (70 mg/dL; <3.9 mmol/L) was similar in both trial arms (12 hrs: 0.07±0.06 vs. 36 hrs: 0.05±0.03, p=0.21). Glycemic excursions during the oral glucose tolerance test were not different after the two fasting periods. Beta-hydroxybutyrate levels were higher after prolonged fasting (p=0.0006). Our study showed that people with type 1 diabetes can safely perform a 36 hours fasting period with a low risk of hypoglycemia and ketoacidosis.